The World of Spore Readers (1) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Esporo is my illustrated guide to agriculture elsewhere. This is how I heard about new rice projects - Mbonani Simão, agricultural supervisor, Moxico